In vivo hippocampal subfield volumes in bipolar disorder: a mega-analysis from the Enhancing Neuro Imaging Genetics through Meta-Analysis Bipolar Disorder Working Group - Haukvik, Unn K.; Gurholt, Tiril P.; Nerland, Stener; Elvsåshagen, Torbjørn; Akudjedu, Theophilus N.; Alda, Martin; Alnæs, Dag; Alonso‐Lana, Silvia; Bauer, Jochen; Baune, Bernhard T.; Benedetti, Francesco; Berk, Michael; et al. (Human brain mapping, 2022)
bipolar disorder subtype, hippocampus, large-scale, lithium, psychosis, structural brain MRI
Zuerst online veröffentlicht am 19. Oktober 2020